Sds22, a PP1 phosphatase regulatory subunit, regulates epithelial cell polarity and shape [Sds22 in epithelial morphology] - Grusche, Felix A (BioMed Central, 2009)
BACKGROUND: How epithelial cells adopt their particular polarised forms is poorly understood. In a screen for genes regulating epithelial morphology in Drosophila, we identified sds22, a conserved gene previously characterised in yeast. RESULTS: In the columnar epithelia of imaginal discs or follicle cells, mutation of sds22 causes contraction of cells along their apical-basal axis, resulting in a more cuboidal morphology. In addition, the mutant cells can also display altered cell polarity, forming multiple layers in follicle cells and leaving the epithelium in imaginal discs. In yeast, sds22 encodes a PP1 phosphatase regulatory subunit. Consistent with this, we show that Drosophila Sds22 binds to all four Drosophila PP1s and shares an overlapping phenotype with PP1beta9c. We also show that two previously postulated PP1 targets, Spaghetti Squash and Moesin are hyper-phosphorylated in sds22 mutants. This function is shared by the human homologue of Sds22, PPP1R7. CONCLUSION: Sds22 is a conserved PP1 phosphatase regulatory subunit that controls cell shape and polarity.